The Effect Of Using Webtoon On Students Writing Skill For The Seventh Grade Students - Rizma Indah Susanti; Erlik Widiyani; Vita Vendityaningtyas (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
The purpose of this study is to ascertain the impact of webtoons on students' narrative writing abilities in texts taught in first grade at SMPN 8 Madiun using the webtoon application. The words "Webtoon app" stand for "website and cartoon," respectively. Therefore, the Webtoon Application is an illustrated cartoon comic that is digitally based. The study was carried out on May 23, 2023. The target population for this study consisted of 32 students from class VII C and 32 students from class VII E. Quantitative research methodology is employed. This study uses a quasi-experimental design to examine how employing a powerful Webtoon application can help students write better narrative texts. Tests consisting of a pre-test and a post-test are used in the data gathering technique. Pre-test Before starting therapy, a post-test was administered to both the experimental class and the control class. The class experiment using the Webtoon Application and the control class refusing to accept or not using the Webtoon Application were the subjects of the post test after receiving treatment. It can be deduced that there is an average difference between the pre-test and post-test learning outcomes, indicating that there has been a significant change in the use of Webtoon Applications in students' ability to write narrative text. The experimental class is 0.000 0.05, so H0 is rejected and Ha is accepted.